EVALUATION OF FABRICATION ERRORS IN TITANIUM COMPOUNDS - Sayliev Ismat Ismatovich; Sokhibov Ibodullo Adizmurodovich (American Journals Publishing, 2022)
The article covers the analysis of components of the cutting errors before choosing the type of control and presents a model of processing error based on analysis of reasons that cause deviation from linear dimensions during machining.
Keywords: characteristics of processing errors, accuracy of dimensions, process equipment accuracy errors, systematic errors, random errors.